How Distributed Data Mining Tasks can Thrive as Knowledge Services. - TALIA, DOMENICO; TRUNFIO, PAOLO (Communications of the ACM, 2010)
The article presents a model of Web 2.0-based information services and knowledge management, focusing on distributed data mining and computational grids. An example of an open service framework for grid-oriented data mining is presented, which includes mobile download applications. Four levels of data mining tasks are delineated and various methods suitable for each level are described. The usefulness of such services is discussed in terms of the semantic web, peer-to-peer systems, cloud computing, knowledge discovery tools, and ambient intelligence computer architectures.